The atlas of endangered peoples - Pollock, Steve (Stephen Thomas) (New York : Facts on File, 1995)
Introduces many problems that threaten human life around the world, both man-made and natural.
Includes index.
Booklist.
School Library Journal.
8.4.
8.4
5-8
Keywords: Environmental degradation; Indigenous peoples; Environmental degradation; Ethnology